KEBERHASILAN USAHATANI KENTANG DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Rasmikayati, Elly; Fatimah, Sri; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
Potatoes are one of the leading food commodities in Indonesia. However, there are indications of a decline in potato production due to a decrease in the national potato harvest area. Apart from that, West Java, as one of the provinces with the highest potato production in Indonesia, has experienced a decline in potato production. The success of potato farming in West Java greatly determines the availability of national potato supplies. The success of potato farming is not only seen from the production results but also the large profits received by potato farmers. This research aims to analyze the characteristics of West Java potato farmers and the factors that influence the success of potato farming in West Java. The analytical tools used are descriptive statistics and multiple regression analysis. The research results show that potato farmers in West Java generally have a low level of education, with an average education equivalent to 7 years or elementary school (SD). However, they have quite a lot of farming experience, an average of 23 years. The average age of farmers is 46 years, which is classified as productive age. As many as 62% of farmers control land with irrigation, and 74% use their own capital to finance their potato farming. The results of the regression analysis show that the success of potato farming in West Java is significantly influenced by experience, age, land area, labor, fertilizer, pesticides, varieties, and participation in land markets. Key-words: Potatoes, characteristics of potato farmers, potato farming inputs, success of potato farming.